On the Application of Inertial Microfluidics for the Size-Based Separation of Polydisperse Cementitious Particulates - Kumar, Aditya; Lewis, Peter; Balonis, Magdalena; Di Carlo, Dino; Sant, Gaurav (Frontiers in Materials, 2015)
The early‐age performance of concrete is determined by the properties of the cementitious binder and the evolution of its chemical reactions. The chemical reactivity, and to some extent, the composition of cementitious particles can depend on particle size. Therefore, it is valuable to physically separate cementing minerals into well‐defined size classes so that the influences of both particle size and composition on reaction progress can be studied without the confounding effects of a broad particle size distribution. However, conventional particle separation methods (e.g., density fractionation, wet sieving, field-flow extraction, ultrasonification-sedimentation) are time-consuming and cumbersome and result in poor particle yields and size-selectivity, thus, making them unsuitable for processing larger volumes of cementitious powders (on the order of grams). This study applies a novel inertial microfluidics (IMF) based procedure to separate cementitious powders on the basis of their size. Special attention is paid to optimizing operating variables to ensure that particles in a fluid streamline achieve unique equilibrium positions within the device. From such positions, particles can be retrieved as per their size using symmetrical outlet configurations with tuned fluidic resistances. The approach is critically assessed in terms of: (1) its ability to separate cementitious powders into narrow size bins, and therefore its feasibility as a fractionation procedure, and (2) quantitatively relating the operating parameters to the particle yield and size selectivity. The study establishes metrics for assessing the ability of IMF methods to classify minerals and other polydisperse particles on the basis of their size.